Edukasi Kesehatan Sebagai Upaya Cegah Penyakit Infeksi Pada Anak - Oematan, Grouse; Ndoen, Honey; Haba Bunga, Eryc; Maku, Grace; Liufeto, Mega; Missa, Yudishinta; Nabuasa, Christin (Bakti Cendana, 2023)
Worms are one of the most common infectious diseases in children. Worm disease is transmitted through food, especially food that has been contaminated with worm eggs. The community service activities are aimed at increasing the knowledge and understanding of school children, as part of an effort to prevent and reduce the prevalence of intestinal worms in children. The service activity begins with distributing pre-test sheets to be filled in by students, this is done to determine the level of students' initial knowledge and understanding of the material to be delivered. Health education efforts are carried out by providing counseling to students regarding clean and healthy lifestyles as well as intestinal worms and prevention efforts. After the counseling was carried out, the team then carried out a post test, to measure students' understanding regarding the material for a clean and healthy lifestyle and intestinal worms. The results of the post test conducted showed an increase in students' knowledge.